Iconographic Program of Kılıçlar kilise in the Context of Posticonoclastic Byzantine Monumental Painting - Vladimirova, Daria V. (Actual Problems of Theory and History of Art, 2024)
The article presents a review of the iconographic program of Kılıçlar Kilise in Cappadocia set within the context of Byzantine monumental painting from the 9th to the 11th century. The analysis of the peculiarities of this program allows us to get a deeper understanding of the processes in Byzantine church decoration in the 9th–10th centuries. During that period some important iconographic developments took place that influenced the iconographic programs of the Late Macedonian and Comnenian periods but left no surviving traces in Constantinople. Kılıçlar Kilise reflects some crucial aspects of these processes. The decoration of its upper zone reflects two well-known types of the dome decoration of multi-domed churches in the metropolitan tradition. The prothesis reveals one of the earliest examples of the “Communion of the Apostles” in Byzantine monumental painting. The Christological cycle of Kılıçlar Kilise comprises two semantic zones: the “upper” zone contains the most significant Gospel scenes, while the “lower” zone provides additional compositions.
Keywords: Cappadocia; Kılıçlar kilise; Macedonian period; monumental painting; iconographic program